Influence of temperature on nitrogen fate during hydrothermal carbonization of food waste. (January 2018) - Wang, Tengfei; Zhai, Yunbo; Zhu, Yun; Peng, Chuan; Xu, Bibo; Wang, Tao; Li, Caiting; Zeng, Guangming
Graphical abstract: Highlights: The nitrogen distribution and evolution in HTC of food waste were investigated. Nitrogen species and amount in products depended on temperature. Amines and N-heterocyclic compounds were identified as main bio-oil-N species. Increasing temperature enhanced incorporation of nitrogen into aromatic heterocycles. Abstract: The influence of temperature (180–260 °C) on the fate of nitrogen during hydrothermal carbonization (HTC) of food waste (FW) was assessed. The distribution and evolution of nitrogen in aqueous products and bio-oil, as well as hydrochar, were conducted. Results suggested that elevated temperature enhanced the deamination and the highest ammonium concentration (929.75 mg/L) was acquired at 260 °C. At temperatures above 220 °C, the total N in the hydrochar became stable, whereas the mass percentage of N increased. Amines and heterocyclic-N compounds from protein cracking and Maillard reactions were identified as the main nitrogen-containing compounds in the bio-oil. As to the hydrochar, increasing temperature resulted in condensed nitrogen-containing aromatic heterocycles (e.g. pyridine-N and quaternary-N). In particular, remarkable Maillard reactions at 180 °C and the highest temperature at 260 °C enhanced nitrogen incorporation (i.e. quaternary-N) into hydrochar.